Reintroduction of the local breeds of sheep and goats in Malta - Blundell R. (Strategies for sheep and goat breeding, 1995)
The number of goats and sheep in Malta has decreased considerably especially in the Maltese local breeds. A program for increasing these Maltese goats began in 1994, and it mainly involves the collection of Maltese breeds of sheep and goats from farmers, importing Maltese goats and sheep from abroad, and then restocking the farmers the selected possible pure Maltese breeds. In parallel with this project, a method using genetic markers is being developed to help in the selection of these animals.
Meeting of the joint FAO/CIHEAM Network on Sheep and Goats, Subnetwork on Animal Resources, 1995/03/26-28, Sidi-Thabet (Tunisia)